2016
DOI: 10.1007/s15010-016-0916-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid molecular diagnosis of infective aortic valve endocarditis caused by Coxiella burnetii

Abstract: We describe a case of Q-fever endocarditis with severe destruction of the aortic valve with perivalvular abscess formation and cardiac failure. The patient needed urgent operative treatment and postoperative critical care. All specimens sent for microbiological examination were negative. Molecular analysis, including fluorescence in situ hybridization of aortic valve tissue combined with PCR and sequencing, led to the correct diagnosis and to appropriate anti-infective treatment. The patient subsequently recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…However, we proved that both FISH and PNA FISH gave better results than immunohistochemistry for the diagnosis of C. burnetii endocarditis and vascular infections. Recently, FISH and molecular assays also enabled the diagnosis of Q fever endocarditis in a patient with severe destruction of the aortic valve with perivalvular abscess formation and cardiac failure (10). Similarly, Aistleitner et al diagnosed a case of Q fever endocarditis by using FISH as well (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we proved that both FISH and PNA FISH gave better results than immunohistochemistry for the diagnosis of C. burnetii endocarditis and vascular infections. Recently, FISH and molecular assays also enabled the diagnosis of Q fever endocarditis in a patient with severe destruction of the aortic valve with perivalvular abscess formation and cardiac failure (10). Similarly, Aistleitner et al diagnosed a case of Q fever endocarditis by using FISH as well (12).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immunohistochemistry often fails to confirm the diagnosis, particularly as a result of early antibiotic treatment. In recent years, fluorescence in situ hybridization (FISH) has been proposed for the diagnosis of Q fever endocarditis using the pan-bacterial probe in both humans (10) and animals (11). Recently, the detection of C. burnetii in heart valve tissues by FISH has also been reported (12).…”
mentioning
confidence: 99%
“…A comparison to the SILVA 16S rRNA database ( Quast et al, 2013 ) revealed that at least one of the reported probes has a perfect match to over 8000 non-target species in the respective region of the 16S rRNA of different bacterial families ( Melenotte et al, 2016 ), resulting in false-positive hybridization signals for all of those species. In the absence of properly tested probes, a previous study used the general bacterial probe EUB ( Amann et al, 1990 ) in conjunction with PCR to diagnose C. burnetii in a patient with IE ( Kumpf et al, 2016 ). The high autofluorescence level of the heart valve tissue was a concern in this research and other studies analyzing tissue parts of endocarditis patients ( Gescher et al, 2008 ).…”
Section: Molecular Basis Of Antimicrobial Resistance In Infective Endocarditismentioning
confidence: 99%
“…The first report on the rapid diagnosis of Q fever endocarditis by PCR of aortic valve tissue was recently published (Kumpf et al, 2016), and a retrospective review of resected cardiac valves/ prostheses from 6401 patients undergoing valve surgery led to an unexpected diagnosis of latent Q fever endocarditis in 14 cases (0.2%) (Grisoli et al, 2014). The case reported here highlights the possibility of identifying and typing C. burnetii in clinical microbiology laboratories without access to biosafety level 3 containment.…”
Section: Discussionmentioning
confidence: 99%